PENETAPAN HARGA JUAL IKAN SEGAR DIKOTA AMBON - Apituley, Yolanda M. T. N; Soukotta, Lilian M; Wattimury, Margie (Balobe: Jurnal Pengabdian Masyarakat, 2023)
One of the objectives of pricing is to achieve stable prices that do not easily rise and fall. With fixed and stable prices, we can avoid potential price wars. This price war can occur when there is a decrease in demand. Product prices are forced down in order to attract buyers. Pricing is influenced by Internal Factors and External Factors. Internal factors include the company's marketing objectives, costs, marketing mix strategies, and pricing methods. Meanwhile, external factors include the nature of the market and demand, competition, and other environmental elements. Selling price is an important thing that is of concern to producers in smoked fish marketing because it will determine the profits obtained for business continuity (Tjiptono, 2015). To achieve a profit desired by producers, one of the ways that needs to be done to attract consumer interest is to determine the selling price of the product appropriately (Waryanto and Nasrulloh, 2014). This is because the price level set will affect the quantity of products sold, because from the consumer's point of view the price is an indicator of the benefits obtained. Fish is one of the fishery products that is easily rotten and requires extra tight handling, so that the quality of the product can be maintained and the price to be offered can be adjusted to existing conditions. Fresh fish is fish that has characteristics including prominent eyes, red gills, complete scales, chewy meat, fresh aroma, and solid tail.